2015
DOI: 10.1116/1.4932579
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Ca, P, and Si on bioactive coatings produced by plasma electrolytic oxidation: The role of electrolyte concentration and treatment duration

Abstract: The objectives of the present study were to produce bioactive coatings in solutions containing Ca, P, and Si by plasma electrolytic oxidation (PEO) on commercially pure titanium, to investigate the influence of different electrolytes concentration and treatment duration on the produced anodic films and to evaluate biocompatibility properties. The anodic films were characterized using scanning electron microscopy, energy-dispersive spectroscopy, atomic force microscopy, and x-ray diffraction and x-ray photoelec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 51 publications
1
31
0
Order By: Relevance
“…Thus, the PEO surface coating was shown to be extremely promising and offered excellent performance in terms of bone repair, as demonstrated in the present study. This surface coating also has superior mechanical [2,17,18] and antimicrobial parameters [21,22,45]. Given the investigations into the favorable structural properties of the PEO surfaces of implants, which were corroborated in the present study by the biological responses of the bone-implant interface, we believe that the next steps include industrial production for human clinical studies.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Thus, the PEO surface coating was shown to be extremely promising and offered excellent performance in terms of bone repair, as demonstrated in the present study. This surface coating also has superior mechanical [2,17,18] and antimicrobial parameters [21,22,45]. Given the investigations into the favorable structural properties of the PEO surfaces of implants, which were corroborated in the present study by the biological responses of the bone-implant interface, we believe that the next steps include industrial production for human clinical studies.…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies of PEO surface characterization have shown that on surfaces coated by this method, an oxide layer is produced, which provides increased wear and corrosion resistance, thermal protection, and the possibility of good adhesion by ions that are important to surface osseointegration, such as Ca and P. This incorporation of Ca and P showed a more homogeneous crystalline structure, as well as large, volcano-like pores, as proven by Scanning electron microscopy. It has also promoted antibacterial properties in microbiological tests [1,2,7,21]. In the study by He et al, the evaluation of commercially pure PEO-treated titanium implants by means of microtomographic and histometric analyses demonstrated that implants with modified surfaces exhibited better bioactivity when compared with pure titanium surfaces [41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The possibility of faster adsorption of the selected ions from the solution (or body fluid) on the anodized surface supports the formation of an apatite layer (Heng et al, ). Calcium also facilitates protein adhesion on the surface of the biomaterial (Marques et al, ). The presence of silicates advances the growth of the bone tissue, cell proliferation, and gene expression (Krząkała et al, ).…”
Section: Introductionmentioning
confidence: 99%